2000
DOI: 10.1067/mhn.2000.106707
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Uvulopalatopharyngoplasty in Unselected Patients with Mild Obstructive Sleep Apnea

Abstract: Overall, these results indicate that UPPP alone in the unselected patient provides little benefit in the management of mild OSA, similar to findings for more severe OSA. Surgeons must use great care in discerning the level of obstruction in the patient with mild OSA to tailor the appropriate retropalatal and/or retrolingual procedures and thereby achieve excellent surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 10 publications
(21 reference statements)
5
58
0
3
Order By: Relevance
“…The overall success rate from mild to severe OSA is reported to be approximately 40 % [9]. Several factors including tongue position, tonsil size, BMI, site of pharyngeal narrowing and severity of the disease have been shown related to the surgical success or failure [10][11][12]. Recently, Zhang et al [13] reported the results of consecutive 119 patients who underwent velopharyngeal surgery including revised UPPP with transpalatal advancement pharyngoplasty.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The overall success rate from mild to severe OSA is reported to be approximately 40 % [9]. Several factors including tongue position, tonsil size, BMI, site of pharyngeal narrowing and severity of the disease have been shown related to the surgical success or failure [10][11][12]. Recently, Zhang et al [13] reported the results of consecutive 119 patients who underwent velopharyngeal surgery including revised UPPP with transpalatal advancement pharyngoplasty.…”
Section: Discussionmentioning
confidence: 96%
“…The study provides evidence that the ST 90 is a unique independent predictor of surgical success with a high sensitivity and high NPV, and can be used by clinicians to allow better selection of patients to achieve maximal outcomes. Several studies have assessed the procedural outcomes and predictors of success in OSA surgery [9][10][11][12][13][14][15][16]. However, the surgical approaches evaluated in these studies vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that surgery should be reserved for patients with mild/ moderate disease, rather than severe disease. However, studies have shown that UPPP is not more effective in treating patients with mild disease, and can even worsen objective parameters such as the apnea-hypopnea index [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons must use great care in discerning the level of obstruction in the patient with mild OSA to achieve excellent surgical outcomes. 11 A prospective randomised study, which compared mandibular advancement appliance with surgery to the soft palate, indicates a success rate of 95% with MAA and 70% with UPPP. 12 Although the patient had previously undergone soft palate reduction, he still opted for orthognathic mandibular advancement, as he did not wish to be committed to protracted use of a mandibular advancement appliance.…”
Section: Discussionmentioning
confidence: 99%